A Rede Feto no Timor-Leste, suas interrelações e o papel das suas lideranças - Abrantes, Laura Soares (2010)
The objective of this dissertation is to analyze the role of the women´s network, Rede Feto, in working within Timorese civil society and how it supports and stimulates its affiliate NGOs through developing their inter-relationships and a common mission. This study describes the day to day participation of Rede Feto leaders as they mentor and assist women in their role of coordination of member organizations. The network of NGOs becomes true instruments of national reconstruction; the women in Rede Feto are the operators of this social movement through their influence on the development of Timorese civil society. The study demonstrates the importance of the network of NGOs to its membership and that their particular characteristics are highly regarded. The foundation of methodological theory for this study is underpinned by gender. Generic theoretical issues within a study of gender are particularized to the context with the aim of catching the localized links. These links or connections are how the responses of the subjects who have participated in this research have been organized. Qualitative research has been undertaken through an ethnographic case study, aiming to deconstruct the experiences and forms of participation of the female leadership of Rede Feto. The study has included different sources of information such as: a) literature reviewed about the theme of the research; b) varied documents about the history of Rede Feto, academic theses, policies about human resources and population needs; c) statistical research using quantitative statistics and information on Timor-Leste; d) material from conduct of 24 semi-structured interviews: Prime Minister of RDTL, Secretary State for Promotion of Equality, 13 Members-Organizations, 7 Deputies of National Parliament and the President of GMPTL; participant observation registered in a diary from observation of the leadership of member organizations in the field. The testimonies of respondents illustrate democratic ideas relating to gender equality. According to the women who are involved in the political sphere and are responsible for the accomplishment of progress, they assume that they were active because others looked to them to take these roles. In fact this study demonstrates that women in leadership positions are responsible for these accomplishments through access to financial resources so that policies can be implemented. In this dynamic, this study identifies that there is a power relationship because there is no power when there is no-one to lead, (this is the inherent relational character of power) and it can be seen also that in all leadership relationships there is an aim to unite and integrate and this consideration is treated as a triadic relationship. The study describes the particularities of context of democratization that is faced in Timor-Leste and portrays the impact on and contribution to an effective re-evaluation of policies.